TV writing on demand : creating great content in the digital era - Landau, Neil (Routledge, 2018)
"TV Writing on Demand: Creating Great Content in the Digital Era takes a deep dive into writing for today's audiences, against the backdrop of a rapidly-evolving TV ecosystem. Amazon, Hulu and Netflix were just the beginning. The proliferation of everything digital has led to an ever-expanding array of the most authentic and engaging programming that we've ever seen. No longer is there a distinction between broadcast, cable and streaming. It's all content. Regardless of what new platforms and channels will emerge in the coming years, for creators and writers, the future of entertainment has never looked brighter.This book goes beyond an analysis of what makes great programming work. It is a master course in the creation of entertainment that does more than meet the standards of modern audiences'"it challenges their expectations. Among other essentials, readers will discover how to:Satisfy the binge viewer: analysis of the new genres, trends and how to make smart initial decisions for strong, sustainable story. Plus, learn from the rebel who reinvented an entire format.Develop iconic characters: how to foster audience alignment and allegiance, from empathy and dialogue to throwing characters off their game, all through the lens of authenticity and relatability.Create a lasting, meaningful career in the evolving TV marketplace: how to overcome trips, traps and tropes, the pros and cons of I.P., use the Show Bible as a sales tool and make the most of the plethora of new opportunities out there."--Provided by publisher.